FIRST RESULTS FROM TIEN-SHAN SURVEY TO SEARCH FOR VARIABLE STARS: LIGHTCURVE ANALYSIS AND VARIABLE STAR CLASSIFICATION - Serebryanskiy, A.; Aimanova, G.; Kondat’eva, L.; Omarov, Ch. (Academic Scientific Journal of Computer Science, 2020)
We present the first results of the light curve analysis of variable stars identified in Tien-Shan survey conducted on Tien-Shan Observatory (TSO) using Zeiss-1000 telescope. Here we report on 33 high amplitude variable stars among which 31 is previously uncatalogued variables. Using data from the StarHorse catalog, as well as results from the MIST project, Color-Magnitude Diagram and appropriate evolutionary tracks were constructed for each field and individual variable star, corresponding to the star’s mass and metallicity. For two objects, we performed spectral observations on the Zeiss-1000 "Zapadny" telescope using a slit spectrograph. The obtained spectra were compared with synthesized spectra. The preliminary identification of variability type of each star is based on parameters of variability (amplitudes and periods) determined from periodograms analysis, evolution stage based on evolutionary track on Color-Magnitude Diagram and, for some targets, on spectral information.